Overview of Teenagers' Knowledge of Type 2 Diabetes Prevention at Semarapura State High School 1 - Ni Made Ary Pradnya Sasmita; Niken Ayu Merna Eka Sari; Ni Kadek Muliawati (CV. AFDIFAL MAJU BERKAH, 2026)
Type 2 diabetes mellitus shows a significant upward trend and is increasingly found in younger age groups, including adolescents. The 2023 Indonesian Health Survey (SKI) reported a prevalence of diabetes mellitus of 11.7% in people aged ≥15 years, reflecting the high national burden of this disease. Regionally, Bali is among the 10 provinces with the highest number of diabetes cases in Indonesia, with an increase in cases from 30,856 to 45,710 in 2024. The results of blood sugar screening by the Bali Provincial Health Office for the period January–May 2025 also showed cases of diabetes in adolescents aged 15–17 years, where 23 of 3,727 adolescents were confirmed to have diabetes and 259 had prediabetes, with the highest number of cases found in Klungkung Regency. Lack of knowledge about prevention is one of the factors that can potentially increase the risk of type 2 diabetes mellitus in adolescents. This study aims to describe the characteristics of respondents and the level of knowledge of adolescents about the prevention of type 2 diabetes mellitus at SMA Negeri 1 Semarapura. The study used a descriptive design with adolescent respondents. The results showed that most respondents were 17 years old (40.6%), female (56.7%), had no family history of diabetes (94.5%), and accessed health information through the internet (45.1%). The level of knowledge was dominated by the good category (90.1%). These findings emphasize the importance of strengthening school-based health education as an early prevention measure for type 2 diabetes mellitus in adolescents